Social Capital and Factors Related to Stroke Risk in Ponorogo Hospital: Structural Equation Model Application - Lailatul Rohmah; Setyo Sri Rahardjo; Bhisma Murti (Masters Program in Public Health, 2020)
Background: Stroke is a non-communicable disease that ranks the second leading cause of death in the world. As many as 17 million pa